(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Crews working in a fast-food chain should be flexible and time management when it comes to service; therefore, there are missing products, and wrong food orders were given to customers due to the mistake of employees assembling food trays the reason they put they the food to the wrong customers instead to the right one. Still, it is mostly not. All of the customers are like that, which will drive customers to complain personally or through sending emails about their experiences to those negligent service crews in a store, which shows bad feedback towards the service crews and even the image of the store. Fast-food chain A respondents are in the age group of 21-30 years old, while in Fast-food chain B, they are in the age group of 31-40 years old, both with mostly female respondents and single. Fast-food chain A respondents are mainly composed of employees, while B comprises customers. There are problems encountered with the possible effects of accidentally misassembled products in terms of quality service, competitive price, completeness, and cutlery and condiments. Based on the results of the paired two-sample t- test, there is no significant difference between the level of satisfaction with Fast-food A (Jollibee) and Fast-food B (Tropical Hut). Employees working in a fast-food chain should be completely groomed and well-mannered and take notes every time they take an order. Clear speech wording and always repeating the guest order to avoid misassembling that can result in customer complaints should be priorities to maintain guest satisfaction. Prioritize and maintain the food they serve with a unique taste so that the customers will always come back, and If an accidentally misassembled occurs, Management of fast food handles customer complaints very well. Problems encountered should be professionally explained by the manager and the employees of a fast-food chain.